Clinical Accuracy of Intraoral Scanner Impressions Compared with Conventional Impressions in Fixed Partial Prostheses: A Systematic Review: Accuracy of Intraoral vs Conventional Impressions in Fixed Prostheses - Shakir, Sheema; Nawaz, Safa; Wisal, Ghazala; Suleman, Ghazala; Waqas, Muhammad; Iqtidar, Zehra (Pakistan Journal of Health Sciences, 2026)
The use of digital impression systems in prosthodontics has gained greater acceptance, but issues surrounding their clinical accuracy compared to traditional elastomeric impressions still exist, particularly for fixed partial prostheses. This comparison is crucial as many practices transition to digital workflows. Objectives: The primary objective of this review was to evaluate the clinical accuracy of intraoral scanner (IOS) impressions versus conventional impressions for fixed partial prostheses. Methods: A systematic search was conducted in PubMed, Scopus, and Cochrane Library for comparative clinical studies published between January 2018 and January 2024. Eligible studies included human trials comparing IOS and conventional impressions for tooth- or implant-supported fixed prostheses. Methodological quality was assessed using a modified QUADAS-2 tool. Results: Fifteen clinical studies met the inclusion criteria. Quantitative analysis revealed marginal gaps for digital workflows ranging from 30 to 90 μm, comparable to the 35–100 μm range observed for conventional methods. Digital impressions demonstrated superior time efficiency and patient comfort. For short-span restorations, IOS accuracy was equivalent to conventional methods; however, conventional techniques showed slightly better stability in long-span implant cases. Conclusions: Current clinical evidence suggests that intraoral scanners provide accuracy comparable to conventional impressions for most fixed partial prostheses, with added benefits in efficiency and patient experience. While caution is advised for complex full-arch cases, IOS can be reliably integrated into routine practice.